Perceived stress and symptoms of post-traumatic stress disorder in nurses: A moderated mediation model of maladaptive cognitive emotional regulation and psychological capital - Xue, Mengxin; Yuan, Yuan; Chen, Hong; Liu, Yongbing; Dai, Minghui; Sun, Huiping; Qu, Jiling; Zhou, Ting; Zhou, Jingxin; Qu, Junchao; Bu, Yuan; Ji, Siqi; et al. (Frontiers in Psychiatry, 2022)
Nurses often face a variety of work-related and life-related stresses that make them more prone to symptoms of post-traumatic stress disorder (PTSD), yet the underlying mechanism of this association is poorly understood. To address this research gap, we investigated the mediating role of maladaptive cognitive emotion regulation strategies in the relationship between perceived stress and PTSD symptoms, and explored whether psychological capital could moderate the direct or indirect effects between perceived stress and PTSD symptoms. Nurses (N = 723) completed a questionnaire about perceived stress, PTSD symptoms, maladaptive cognitive emotion regulation strategies and psychological capital. After controlling for gender, age and work department, perceived stress was positively correlated with PTSD symptoms. Maladaptive cognitive emotion regulation strategies partially mediated this relationship. Psychological capital moderates the effects of perceived stress and maladaptive cognitive emotion regulation strategies on PTSD symptoms. Specifically, the positive correlation between perceived stress and PTSD symptoms was stronger among nurses with low levels of psychological capital than among nurses with high levels of psychological capital. At the same time, the positive correlation between maladaptive cognitive emotion regulation strategies and PTSD symptoms was stronger in nurses with a low level of psychological capital. Therefore, cognitive strategies and interventions oriented toward psychological capital may alleviate the PTSD symptoms of nurses in stressful situations.